Case report of a unique phenomenon: leptomeningeal spread in glioblastoma multiforme - Farhan, Kanza; Ahmed, Yumna; Shaukat, Fatima (Journal of the Pakistan Medical Association, 2025)
Leptomeningeal spread (LMS) of glioblastoma multiforme (GBM) is a rare event, presenting challenges in both diagnosis and treatment. Here, we describe the case of a 59-year-old GBM patient who experienced LMS during his treatment. Despite multimodal therapy, including surgery, chemotherapy, and radiotherapy, the patient’s condition rapidly deteriorated. The case illustrates the difficulty in treating GBM and the restricted ability of available treatments to stop LMS. This manifestation is uncommon, which highlights the need for increased awareness, ongoing study, and development of tailored treatments. Key factors influencing LMS include tumour size, age, and anatomical location. Diagnostic challenges arise due to the rarity of LMS in GBM and its atypical presentation. Therapeutic interventions targeting LMS are lacking, with poor prognosis and low survival rates. To improve patient outcomes, more studies should be done on creating efficient treatment regimens and figuring out the markers associated with LMS development in GBM.